Cultural diversity and growth of international firms - Francisco, F.R.R.; Kovalenko, O.; Kovalenko, S. (Економічний вісник Донбасу, 2016)
This article deals with the impact of national cultures on growth of international firms. It critically reviews the major contributions of the literature on this field. Starting from the seminal work of Hofstede we conclude that due to the continuous growth of globalization and the tremendous social changes, old theories such as Hofstede’s (1984) study could not be fully applicable in today’s societies. Thus, these studies should be continuously updated and the need for further research is mandatory in this field. У статті розглядається вплив національних культур на розвиток міжнародних фірм. Було здійснено критичний огляд внеску наукової літератури у цю сферу. Беручи до уваги основоположну роботу Хофстеде, можна зробити висновок, що через невпинну/неперервну глобалізацію та надзвичайні соціальні зміни, старі теорії, такі як праця Хофстеде (1984), не змогли би знайти свого застосування у сучасному суспільстві. Таким чином, ці наукові праці слід постійно оновлювати та необхідним є подальше дослідження у цій сфері. В статье рассматривается влияние национальных культур на развитие международных фирм. Был проведен критический анализ вклада научной литературы в эту сферу. Принимая во внимание основополагающую работу Хофстеде, можно сделать вывод, что из-за непрерывной глобализации и огромных социальных изменений, старые теории, такие как работа Хофстеде (1984), не смогли найти своего применения в современном обществе. Таким образом, эти научные работы следует постоянно обновлять и последующее исследование в этой сфере является необходимым.